Dynamics of Infinitesimal Particle in the Framework of Photo-Gravitational Restricted Three-Body Problem - Mia, Rajib (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we study the dynamics of small particle in the framework of the photo-gravitational restricted three body problem in the binary stellar masses. In this work, we consider three binary stellar systems Kepler-34, Kepler-35 and Kepler-16. The dynamics of the test particle in these three systems is studied in terms of the Poincar\’e surfaces of section method and the finite-time local Lyapunov exponents. We have computed full Lyapunov spectrum for this three binary systems. %Also maximum Lyapunov characteristic exponents (mLCEs) can be used as an indicator and a measure of the chaotic motion. We have obtained mLCEs with the help of numerical integration of equations of motion in the planar circular restricted three body problem considering both primaries as radiating. Poincar\’e surfaces of section for different values of radiation parameter are obtained and observed the corresponding changes accordingly. Also, we have obtained orbits and corresponding Poincar\’e surface of sections for all systems. Moreover, using actual values of radiation parameter, we have computed Poincar\’e surface of section for different values of Jacobi constant.